5a+2=6x-1

Simple and best practice solution for 5a+2=6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5a+2=6x-1 equation:


Simplifying
5a + 2 = 6x + -1

Reorder the terms:
2 + 5a = 6x + -1

Reorder the terms:
2 + 5a = -1 + 6x

Solving
2 + 5a = -1 + 6x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 5a = -1 + -2 + 6x

Combine like terms: 2 + -2 = 0
0 + 5a = -1 + -2 + 6x
5a = -1 + -2 + 6x

Combine like terms: -1 + -2 = -3
5a = -3 + 6x

Divide each side by '5'.
a = -0.6 + 1.2x

Simplifying
a = -0.6 + 1.2x

See similar equations:

| -(4y-3u-3)= | | 2f+3=11f+-24 | | 3p=-4 | | -2x-4-6y+15=-11 | | -2x-4-6y+15=11 | | -b/2(a) | | 9c=4 | | 6x/3x | | -2+7x=45 | | 4d+(-11)=2d+7 | | 2x-11+4x-22=180 | | X+51=-62 | | 15=4x-55 | | 2m+9=7m-36 | | 9x^2+4x-3=7x^2-2 | | C=5/2k-47 | | y=0.036x^2-2.8x+62.57 | | 4(4w+3)*3=-11 | | C=5/2k-37 | | (-7x+13)(-x-8)=0 | | 5(2x+3)-6(-2x+1)=9(x-2) | | 2[x-2(x-1)]-3(3y-5)=-11 | | (2x-5)2-(x+1)2=7x | | -5(2t+2)=20 | | n+(-12)=3n | | X-2x+3=4x+2 | | 9x-9=9-8x | | 8x-16-2x=34 | | 12ab-28bc+20ac=0 | | x^(2/#)=1/3 | | 10x=0.000001 | | 3t^2-16t+21=0 |

Equations solver categories